(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
In this article presented methodical aspects of increase of efficiency of teaching physics in the higher technical educational institutions, and also examines the didactic conditions of use in the educational process to ensure intra-subject continuity between theoretical and practical knowledge